A tabu search algorithm for determining the economic design parameters of an integrated production planning, quality control and preventive maintenance policy. (1st January 2011) - Rahim, Abdur; Shakil, Muhammad
Production, quality and management are three important aspects in an industrial process and in engineering management. In this work, an integrated model of economic production quantity (EPQ), economic design of an